Solar PV Tracker System for Traffic Light Application - Wan Hazirudin, Wan Nur Sabrina; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2022)
Solar energy is becoming more essential, particularly in rural areas. However, the conventional photovoltaic cell conversion efficiency is limited. This project will develop a solar PV traffic signal tracker. This study’s objective is to track the sun’s position. The project has two parts: software and hardware. The device used four light-dependent resistors (LDR) to detect sunlight intensity. The two 180° servo motors are used to move the panel towards the sun. In Proteus, the solar tracker and traffic light system are designed. It was compared to a static solar panel. Finally, the system has shown its potential to gather maximum sunlight.